Contemporary issues in business and economics - Chia-Lin Chang; Duc Hong Vo (MDPI, 2020)
This book is a collection of high-impact papers accepted and presented at the 2019 Vietnam's Business and Economics Research Conference (VBER2019) organised by Ho Chi Minh City Open University held on 18th-20th July 2019. The Special Issue is associated with a broad coverage of the contemporary issues in Business and Economics in Vietnam and other emerging markets reflecting a key theme of VBER2019: Vietnam's Place in the Asia Pacific Region. A total of 14 papers were published from more than the 120 submissions to the VBER2019 Conference. Published papers had been undergone a rigorous reviewing process conducted by the Journal of Risk and Financial Management. The papers incorporated in this book address contemporary issues in business and economics from Vietnam and other emerging markets in the Asian region from various angles such as economics, finance, and statistics to management science.
Keywords: 330; Wirtschaftslage; Entwicklung; Vietnam; Asiatisch-pazifischer Raum